P687Complement system modulation as a target for treatment of arrhythmogenic cardiomyopathy. (15th July 2014) - Mavroidis, M; Davos, C; Varela, A; Kostavasili, I; Tsilafakis, K; Vater, A; Van Tintelen, J P; Capetanaki, Y
Abstract: Objectives, Background: Inflammation may contribute to disease progression in arrhythmogenic cardiomyopathy (AC) however, its role in this process is unresolved. Our goal was to delineate the pathogenic role of the complement system in a new animal model of AC and its involvement in human disease. Methods and Results: By cardiac histology, echocardiography, and electrocardiography we have demonstrated that the desmin-null mouse (Des-/-) recapitulates most of the pathognomonic features of human AC. Massive complement activation was observed in the Des-/- myocardium in areas of necrotic cells debris and inflammatory infiltrate. Analysis of C5aR-/-Des-/- double-null animals and a pharmaceutical approach using the C5a-neutralizing Spiegelmer were used to delineate the pathogenic role of the complement system in the disease progression. Our findings indicate that inhibiting C5aR (CD88) signaling appreciably improves cardiac function, histopathology, and arrhythmias. Containment of the inflammatory reaction at the initiation of cardiac tissue injury (at 2-3 weeks of age) with a consequently reduced myocardial remodelling and the absence of a direct long lasting detrimental effect of C5a-C5aR signaling on cardiomyocytes could explain the beneficial action of C5aR ablation in Des-/- cardiomyopathy. We substantiated the relevance of these findings to human pathophysiology by demonstrating, for the first time, significant complement activation in the cardiac tissues from patients with AC. Conclusions: Complement could be a valid target for treatment/amelioration of AC.